Moderate wildfire severity favors seed removal by granivores in a Mexican pine forest - Cadena-Zamudio DA; Cadena-Iñiguez J; Aguirre-Medina JF; Cadena-Zamudio JD; Arispe-Vázquez JL; Barrera-Guzmán LA; Ayvar-Serna S; Díaz-Nájera JF (iForest - Biogeosciences and Forestry)
Wildfires are critical to the ecological dynamics of communities in temperate forests. However, their frequency and severity have increased significantly in recent decades due to human activities, negatively affecting flora, fauna, and ecosystem processes. Among the primary interactions for the natural regeneration of forests is seed removal, which promotes secondary seed dispersal and predation. This study evaluated artificial seed removal under different wildfire severities in a pine forest on the eastern edge of the Trans-Mexican Volcanic Belt. An experiment of differential exclusion of vertebrates and invertebrates was carried out, considering two treatments: totally exposed seeds and seeds with exclusion of vertebrates in the unburnt forest, moderate and high severity fire. Our results showed a higher seed removal by vertebrates (birds and rodents) in the wildfire moderate severity treatment and in the time elapsed since wildfire occurrence; however, excluding vertebrates decreased the seed removal rate after the fire. Therefore, moderate-severity sites are an important factor in the communities of granivores that influence seed removal patterns in the temperate forest of Veracruz, Mexico. The findings underscore the importance of considering fire severity gradients in forest management strategies, particularly in fire-adapted ecosystems. As climate change alters fire regimes worldwide, understanding how different fire severities affect ecological interactions such as granivory is essential for promoting forest resilience and biodiversity.